Welcome to Westonci.ca, your ultimate destination for finding answers to a wide range of questions from experts. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.

x^2-6x+1=0 solve by completing square

Sagot :

the answer is x= +- 2 square root of 2 + 3

Answer:

x = 3 ± 2[tex]\sqrt{2}[/tex]

Step-by-step explanation:

x² - 6x + 1 = 0 ( subtract 1 from both sides )

x² - 6x = - 1

to complete the square

add ( half the coefficient of the x- term )² to both sides

x² + 2(- 3)x + 9 = - 1 + 9

(x - 3)² = 8 ( take square root of both sides )

x - 3 = ± [tex]\sqrt{8}[/tex] = ± 2[tex]\sqrt{2}[/tex] ( add 3 to both sides )

x = 3 ± 2[tex]\sqrt{2}[/tex]

Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. Westonci.ca is here to provide the answers you seek. Return often for more expert solutions.